Perancangan Desain Lembar Kerja Faceless Untuk Anak Muslim Usia Dini - Yasmin Firda Safira; Masnuna Masnuna (Lembaga Pengembangan Kinerja Dosen, 2024)
Worksheet for children is one of the learning tools that can be used as early childhood education media. Early childhood refers to children in the age range of 0-6 years old. As we all know, this age is crucial and influential for the future of these children. Therefore, one of the roles that parents can play is to find suitable learning media, and one of them is by using children's worksheets. Children's worksheets are often associated with images of living beings such as humans and animals.To address the concerns of Muslim parents who may consider drawing living beings as prohibited, a faceless worksheet named